(untitled) (Journal of the College of Basic Education, 2022)
This research aimed to the Evaluation of Practice of Camle Breeders in Some Governorates of Middle Euphrats / Iraq, The process of evaluation of Practice of Camle took stages, these stages are thefirst: Literatures&Folders Extension in field of farm animals, containing of fifth field , Thrity Four items the second: A preliminary of Practice of Camle Scale was showed to a group of experts and specialized persons in agricultural extension field ,veterinary & animal products, to express their opinions about fields and items of the of Practice of Camle scale and its fitness.the. third:Used the tri of Practice of Camle scale consists of Weak, Partially and Complete , and put degrees of the tri scale Practice of Camle according to:Weak 1 degrees , Partially 2 degrees and Complete 3 degrees. four stage : determining the groups of criteria to evaluate of Practice of Camle. Fife stage : Surveying of Practice of Camle .six stage :: Compare between criteria and surveying , and Judgment about Practice of Camle. . The research population is(1800 breeder) in Some Governorates of Middle Euphrats(Al-Muthana , Thiqar , Qadisiya , Babylon) / Iraq . A sample was randomly chosen using the stratified method a percentage of (10%) the numbers are (180 breeder) . A questionnaire used to collect datas from the sample.The statistical tools used are the Weighed Mean,Alpha cronbach coefficient. This research ended to the Evaluation of Practice of Camle Breeders in Some Governorates of Middle Euphrats / Iraq stands in the medium level. The research recommendations that aiming to support the Evaluation of Practice of Camle Breeders in Some Governorates of Middle Euphrats / Iraq,that reflected a positive improving productivity and production of farming system